Intracavernous Schwannoma Characterized With 18F-FDG, 68Ga-DOTATOC, and 18F-Choline PET. (February 2022) - Farce, Julien; Lecouillard, Isabelle; Carsin Nicol, Béatrice; Bretonnier, Maxime; Girard, Antoine
Abstract : Abstract: We report the case of a 75-year-old man with history of prostate cancer whose left intracavernous lesion was successfully characterized by 3 PETs performed successively with different tracers. This poorly characterized tumor was initially discovered on an MRI conducted to investigate an acute diplopia and slowly growing during follow-up. On 18 F-FDG PET, the lesion showed no significant uptake, and no extracranial lesion was found nor did it have increased 68 Ga-DOTATOC uptake. Finally, this tumor displayed a high 18 F-choline uptake, and no extracranial lesion was revealed with this tracer. The diagnosis of schwannoma without malignancy criterion was proven by biopsy.